Kinetic features of xylan de-polymerization in production of xylose monomer and furfural during acid pretreatment for kenaf, forage sorghums and sunn hemp feedstocks - Kamireddy, Srinivas Reddy; Kozliak, Evguenii I.; Tucker, Melvin; Ji, Yun (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: A kinetic study of acid pretreatment was conducted for sorghum non-brown mid rib (SNBMR) (Sorghum bicolor L Moench), sorghum-brown mid rib (SBMR), sunn hemp (Crotalaria juncea L) and kenaf (Gossypiumhirsutum L), focusing on rates of xylose monomer and furfural formation. The kinetics was investigated using two independent variables, reaction temperature (150 and 160°C) and acid concentration (1 and 2 wt%), with a constant dry biomass loading of 10 wt% and a treatment time up to 20 min while sampling the mixture every 2 min. The experimental data were fitted using a two-step kinetic model based on irreversible pseudo first order kinetics at each step. Varied kinetic orders on the acid concentration, ranging from 0.2 to >3, were observed for both xylose and furfural formation, the values depending on the feedstock. The crystallinity index of raw biomass was shown to be a major factor influencing the rate of both xylose and furfural formation. A positive correlation was observed between the activation energy and biomass crystallinity index for xylose formation.Keywords: acid pretreatment, sunn hemp, sorghum brown-mid rib (BMR), sorghum non brown- mid rib (SNBMR), kenaf, reaction kinetics, activation energy, reaction orderDOI: 10.3965/j.ijabe.20140704.010Citation: Kamireddy S R, Kozliak E I, Tucker M, Ji Y. Kinetic features of xylan de-polymerization in production of xylose monomer and furfural during acid pretreatment for kenaf, forage sorghums and sunn hemp feedstocks. Int J Agric & Biol Eng, 2014; 7(4): 86-98.